The Influence of Temperature on Swelling Characteristics of Compacted Bentonite for Waste Disposal - Sharif Moniruzzaman Shirazi (EnvironmentAsia, 2010)
A series of experiment was conducted to find out the temperature effect on swelling characteristics of compacted bentonite. The expansion of partly saturated bentonite affects the volume change of air in the specimen respect to initial dry density. Swelling pressure reaches nearly maximum when degree of saturation of specimen is about 95% for all initial dry densities (1.29 ~ 1.95 g/cm3) in swelling pressure test using temperature 20 ~80°C. Initial dry density and temperature are the governing parameter to control the swelling pressure and deformation of compacted bentonite. To predict the swelling pressure an equation has been proposed in relation to content of montmorillonite, temperature and initial dry density of bentonite. The maximum difference between the experimental values and the fitting of this equation is 15% on an average.